1983
DOI: 10.1002/jcp.1041140306
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of angiotensin‐stimulated sodium transport in cultured smooth muscle cells from rat aorta

Abstract: Angiotensin peptides (AI, AII, AIII) increased the rate of Na+ accumulation by smooth muscle cells (SMC) cultured from rat aorta. The stimulatory effect of AII on Na+ uptake was observed when Na+ exodus via the Na+/K+ pump was blocked either by ouabain or by the removal of extracellular K+. AII was at least ten times more potent than AIII and about 100 times more potent than AI in stimulating Na+ uptake. Saralasin had little effect on Na+ uptake by itself but almost completely blocked the increase caused by AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 52 publications
0
57
0
Order By: Relevance
“…lOB suggest it would not. In addition, [Na+]i may also increase as a result of activation by agonists in some smooth muscles (Smith & Brock, 1983;Aaronson & Jones, 1988). The driving force for reduction of [Ca2+]i via the exchange may therefore be reduced following pharmacomechanical coupling, at least until the Na+ gradient is restored.…”
Section: Discussionmentioning
confidence: 99%
“…lOB suggest it would not. In addition, [Na+]i may also increase as a result of activation by agonists in some smooth muscles (Smith & Brock, 1983;Aaronson & Jones, 1988). The driving force for reduction of [Ca2+]i via the exchange may therefore be reduced following pharmacomechanical coupling, at least until the Na+ gradient is restored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DNA synthesis in VSMC can be stimulated by peptide growth factors (14,19,20), phorbol esters (13), and catecholamines (2). In addition, both growth factors (14, 19) and phorbol esters (13) have been shown to also stimulate Na/H exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Another agent shown to be mitogenic for VSMC is angiotensin II (6). In addition, Smith et al have demonstrated that angiotensin II could activate Na/H exchange in VSMC (20). Recently, my laboratory has shown that DNA synthesis and Na/H exchange in VSMC could be stimulated by biologically active phorbol esters such as 12-O-tetradecanoyl phorbol-13-acetate (TPA) (13).…”
mentioning
confidence: 99%
“…It was subsequently demonstrated that the Na+ influx is via an electroneutral and amiloride-sensitive Na+-H+ exchanger (43,(45)(46)(47) (51). The use of amiloride inhibition of cell growth to prove the importance of Na'-H' exchange has been criticized because of the ability of the drug to directly inhibit protein synthesis (52 (61), lys-bradykinin in human fibroblasts (62), and vasopressin (63). Insulin has been observed to increase Na+-H+ countertransport in skeletal muscles cells (42); in fibroblasts it has synergistic actions with EGF suggesting a different mechanism of action (59).…”
Section: Introductionmentioning
confidence: 99%